IMPLEMENTASI INVENTORY MANAGEMENT SYSTEM SEBAGAI KEWAJIBAN BAGI PERUSAHAAN KAWASAN BERIKAT - Daryatno, Andreas Bambang; Suryapon, Michelle Agustine; Desinda, Yohana Louji (Jurnal Serina Abdimas, 2024)
For companies that receive bonded zone facilities, tax obligations when importing goods and local purchases will be suspended or not collected as long as the products they produce are exported. The tax obligations that receive exemption or deferral relate to imported goods purchased from Import Duty, Sales Tax on Luxury Goods, Value Added Tax, Income Tax Article 22, while local purchases are in the form of Value Added Tax. With the above facilities, the government, through the Director General of Customs and Excise, carries out very strict supervision of materials and capital goods that receive tax exemption facilities, either directly by placing Customs officers in each company that obtains bonded zone (Hangar) facilities and indirect supervision. via a network or internet connected to CCTV in several locations within the company so that the Central Customs, BC Tanjung Priok, BC Soekarno Hatta and BC Halim offices can see, monitor and supervise all day long (24 hours) the company's activities. To facilitate remote monitoring, customs requires all companies to implement a cloud-based Inventory Management System (IMS). By implementing IMS, customs authorities wherever they are can access the company's Information Technology Inventory either via PC, Laptop, Tab or even mobile phone. If a company does not implement IMS, it is possible that the bonded zone facility will be revoked by customs authorities. Partner problems: the threat of revocation of permits for the following area facilities, even though the company has implemented inventory control with accurate software but is not yet cloud based and the traceability of material goods and capital goods is felt by customs authorities to be inadequate. The solution to overcome partner problems, so that the Company's activities can run well and remain in the green lane of Customs and Excise is to implement a cloud-based Inventory Management System (IMS). The resulting output is that the Company can meet the demands of Customs and Excise, both in terms of access and traceability of all goods that receive facilities. The system can also be accessed by the BOD and Company internally wherever they are. The method used is through assistance with system implementation so that it runs quickly, precisely and efficiently.